Survey for Vehicle Number Detection Technique - Kaur, Ramneek; Kaur, Supreet (International Journal of Computer Sciences and Engineering, 2020)
There are very large number of vehicles in India as it is very densely populated country across world. So, there is a need of detecting vehicles accurately using traffic management system. This system detects the image of the number plate of a vehicle from video using video processing with raspberry pi and the number is extracted using different methods and algorithms. The system is applicable for entrances of gates in colleges and highly restricted areas. When any vehicle passes by the system the video is captured and then video is converted into images. In this review paper for number plate recognition of vehicles we had discussed various techniques that were used in to achieve recognition.